Integrasi Pendidikan Karakter dalam Filsafat Pendidikan Islam - Duwi Hastreni; Nila Rif’atun Na’im; Ahmad Ainul Yakin; Ahmad Husin (Jurnal Wahana Literasi Pendidikan, 2026)
Character education has become a central issue in contemporary education due to the increasing moral crisis and the decline of social ethics. From an Islamic perspective, character education cannot be separated from the concept of akhlaq (moral conduct), which constitutes the primary objective of education. This article aims to analyze the integration of character education within the philosophy of Islamic education through a library research approach. The findings indicate that the philosophy of Islamic education provides ontological, epistemological, and axiological foundations for character formation. This integration is reflected in the objectives of Islamic education, the concept of insān kāmil (the complete human being), exemplary based teaching methods, and the internalization of spiritual values in the educational process. Through this integration, Islamic education is capable of producing generations who are knowledgeable, faithful, and possess noble character.